Knee joint biomechanics following arthroscopic partial meniscectomy - Sturnieks, Daina; Besier, Thor; Mills, Peter; Ackland, Tim; Maguire, Ken; Stachowiak, Gwidon; Podsiadlo, Pawel; Lloyd, David (John Wiley & Sons, Inc., 2008)
We investigated spatiotemporal data, joint kinematics, and joint kinetics during gait in a group of subjects who had recently undergone arthroscopic partial meniscectomy and compared the results to those of healthy controls. Gait analysis was performed on 105 pain-free meniscectomy patients and 47 controls, walking at a self-selected speed. The meniscectomy population was comparable to controls in spatiotemporal parameters and knee kinematics. However, they had reduced range of motion (ROM) and lower peak moments in the sagittal plane on the operated limb compared to the nonoperated limb. Compared to controls, the meniscectomy patients had significantly larger knee adduction moments over stance, even after accounting for their greater body weight. These differences likely increase articular loads on the medial compartment of the tibiofemoral joint and may contribute to the high risk of knee osteoarthritis following arthroscopic meniscal surgery.